7-5(x-2)=5-3(x+3)

Simple and best practice solution for 7-5(x-2)=5-3(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-5(x-2)=5-3(x+3) equation:


Simplifying
7 + -5(x + -2) = 5 + -3(x + 3)

Reorder the terms:
7 + -5(-2 + x) = 5 + -3(x + 3)
7 + (-2 * -5 + x * -5) = 5 + -3(x + 3)
7 + (10 + -5x) = 5 + -3(x + 3)

Combine like terms: 7 + 10 = 17
17 + -5x = 5 + -3(x + 3)

Reorder the terms:
17 + -5x = 5 + -3(3 + x)
17 + -5x = 5 + (3 * -3 + x * -3)
17 + -5x = 5 + (-9 + -3x)

Combine like terms: 5 + -9 = -4
17 + -5x = -4 + -3x

Solving
17 + -5x = -4 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
17 + -5x + 3x = -4 + -3x + 3x

Combine like terms: -5x + 3x = -2x
17 + -2x = -4 + -3x + 3x

Combine like terms: -3x + 3x = 0
17 + -2x = -4 + 0
17 + -2x = -4

Add '-17' to each side of the equation.
17 + -17 + -2x = -4 + -17

Combine like terms: 17 + -17 = 0
0 + -2x = -4 + -17
-2x = -4 + -17

Combine like terms: -4 + -17 = -21
-2x = -21

Divide each side by '-2'.
x = 10.5

Simplifying
x = 10.5

See similar equations:

| 11-9x=29-16x | | -9+2z=9z+12 | | 2(x-1)-3(2-x)+4(1-x)=0 | | -23-4x=9-8x | | -134-7x=8x+16 | | -5(k+5)+5k= | | 5(b-4)+25= | | 0=3(2-3x)-7(x-3) | | 10+2(4y+3)= | | 3x-2(12-x)=4(2x-3)+3(x+1) | | 6-5c=-14 | | 6(1-x)+4=3(2-x)-4 | | 4x+10=90-6 | | 40-2(x+1)=90 | | 4k+6=6k-2 | | 6(2x+1)+7=9x+1 | | 6x+9=-119-10x | | 3(7x-1)+8(3-2x)=1 | | -2*5= | | 5(2x+3)-3(x+1)=5 | | 8(x-2)-2(2x-1)=2x+1 | | -2(5r+3)= | | 5a+30b=25 | | 5(3x-4)=8x+1 | | 6a-4=8 | | 3(10a)= | | 2x-3(2-x)=4 | | 4(x+3)-2=2 | | 3(x+1)+2(2x+7)=3 | | 5(f-12)=9+5f | | 6x+y-8x+y= | | 3(2x+5)+5(x-1)=-1 |

Equations solver categories